Correction: Glycosylation enhances the aqueous sensitivity and lowers the cytotoxicity of a naphthalimide zinc ion fluorescence probe. Issue 60 (4th August 2015) - Dong, Lei; Zang, Yi; Zhou, Dan; He, Xiao-Peng; Chen, Guo-Rong; James, Tony D.; Li, Jia
<x xml:space="preserve">Abstract</x> Correction for 'Glycosylation enhances the aqueous sensitivity and lowers the cytotoxicity of a naphthalimide zinc ion fluorescence probe' by Lei Dong et al., Chem. Commun., 2015, DOI: 10.1039/c5cc04357c.